Orthotics and prosthetics in rehabilitation - Chui, Kevin K; Jorge, Milagros; Yen, Sheng-Che; Lusardi, Michelle M (St. Louis, Missouri : Elsevier, 2020)
Gain a strong foundation in the field of orthotics and prosthetics! Orthotics and Prosthetics in Rehabilitation, 4th Edition is a clear, comprehensive, one-stop resource for clinically relevant rehabilitation information and application. Divided into three sections, this text gives you a foundation in orthotics and prosthetics, clinical applications when working with typical and special populations, and an overview of amputation and prosthetic limbs. This edition has been updated with coverage of the latest technology and materials in the field, new evidence on effectiveness and efficacy of interventions and cognitive workload associated usage along with enhanced color photographs and case studies - it's a great resource for students and rehabilitation professionals alike.
Building baseline knowledge -- Orthotics and prosthetics in rehabilitation: multidisciplinary approach / Milagros Jorge -- Aging and activity tolerance: implications for orthotic and prosthetic rehabilitation / Ethan A. Hood, Kevin K. Chui, and Michelle M. Lusardi -- Motor control, motor learning, and neural plasticity in orthotic and prosthetic rehabilitation / Donna M. Bowers, Andrea Oberlander, Kevin K. Chui, Kimberly Leigh Malin, and Michelle M. Lusardi -- Evidence-based approach to orthotic and prosthetic rehabilitation / Jeremy E. Hilliard, Kevin K. Chui, Tabitha D. Galindo, And Michelle M. Lusardi -- Clinical assessment of gait / Olfat Mohamed and Heather Appling -- Materials and Technology / Geza F. Kogler, Michael Bridges, Jeremy E. Hilliard, And Kevin K. Chui -- Footwear: foundation for lower extremity orthoses / Daniel A. Riddick, Daniel H. Riddick, And Milagros Jorge -- Orthoses in rehabilitation -- Foot Orthoses / Elicia Pollard -- Principles of lower extremity orthoses / Eric Folmar, Heather Jennings, And Michelle M. Lusardi -- Neurological and neuromuscular disease implications for orthotic use / Donna M. Bowers and Kevin K. Chui -- Orthoses for knee dysfunction / S. Tyler Shultz -- Orthoses in orthopedic care and trauma / Melissa Thacker, Bradley Conner, and Michelle M. Lusardi -- Orthoses for spinal dysfunction / Theresa E. Leahy and Sharidy MacCord -- Orthoses in the management of hand dysfunction / Brian J. Wilkinson -- Orthoses in burn care: splinting, orthotics, and prosthetics in the management of burns / R, Scott Ward -- Prescription wheelchairs: seating and mobility systems / Susan H. Ventura and Katherine Bendix -- Prostheses in rehabilitation -- Etiology of amputation / Milagros Jorge -- High-risk foot and wound healing / Milagros Jorge and Eddie J. Traylor -- Amputation surgeries for the lower limb / Patrick D. Grimm and Benjamin K. Potter -- Postoperative and preprosthetic care / Tamara Gravano and Michelle M. Lusardi -- Understanding and selecting prosthetic feet / Kevin Carroll, John Rheinstein, and Elicia Pollard -- Postsurgical management of partial foot and syme amputation / Jonathan Day and Milagros Jorge -- Transtibial prosthetics / Todd Dewees -- Transfemoral prostheses / Joan E. Edelstein and Kevin K. Chui -- Prosthetic options for persons with high-level and bilateral amputation / Milagros Jorge, J. Douglas Call and Tyler Manee -- Early rehabilitation in lower extremity dysvascular amputation / Julie D. Ries and Kelly J. Negley -- Advanced rehabilitation for people with microprocessor knee prostheses / Christopher K. Wong and Joan E. Edelstein -- Athletic options for persons with limb loss / Carol Pierce Dionne and Joshua Thomas Williams -- Rehabilitation for children with limb deficiencies / Joan E. Edelstein and Susan Ann Denninger -- Prosthetic options for persons with upper extremity amputation / Susan Spaulding and Tzurei Chen -- Rehabilitation for persons with upper extremity amputation / Annemarie E. Orr.
Lusardi, Michelle M. appears first in earlier editions.
Includes bibliographical references and index.
Keywords: Orthopedic apparatus; Prosthesis; Orthopedic implants; People with disabilities -- Rehabilitation; Artificial Limbs; Orthotic Devices; Rehabilitation